Mental well-being and diversity, equity, and inclusiveness in the veterinary profession: Pathways to a more resilient profession - Timmenga, Florentine Scilla Louise; Jansen, Wiebke; Turner, Patricia V.; De Briyne, Nancy (Frontiers in Veterinary Science, 2022)
Mental well-being (MWB) and diversity, equity and inclusiveness (DEI) continue to be critical within the veterinary profession but there is little information regarding how professional as-sociations around the world tackle these issues. A mixed-method study including an international online survey in English (n=137 responses via snowball sampling), fourteen interviews and two webinars was used to identify the availability and impact of MWB and DEI support programs for veterinarians. Survey results showed that more veterinary organizations designated MWB and DEI challenges (54%, n=43/79 and 58%, n=45/78, resp.) as a key priority area than veterinary clinics (26%, n=15/57 and 33%, n=19/57, resp.). Whereas MWB support programs were available in a moderate number of mainly English-speaking countries, DEI support programs were available in only a few countries and focused primarily on specific groups, with an unknown impact due to their recent implementation. Universally, survey respondents believed activities for specific groups, such as MWB webinars, training and awareness campaigns as well as MWB/DEI helplines and DEI peer-to-peer support programs had a high impact (median 3.5-4/5) yet were underemployed by both veterinary organization and veterinary clinics. Further feedback from respondents during focused interviews indicated that requiring initial and continuing training as well as tailored group activities would be most beneficial to improve MWB/DEI throughout the veterinary professional career. There are many areas of the intersection between MWB and DEI that remain to be elucidated in future studies. Having a sufficient sample size, improve accessibility and addressing varying cultural perceptions are main challenges, as seen in our study. To truly address MWB and DEI disparities, change is also needed in veterinary workplace culture and environment. In conclusion, raising awareness for an inclusive profession, including increasing openness and acceptance to enhance DEI and destigmatizing MWB challenges are needed to ensure a thriving, modern veterinary profession.